2016
DOI: 10.1007/s13361-016-1432-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Added Hydrogen on Noble Gas Discharges Used as Ambient Desorption/Ionization Sources for Mass Spectrometry

Abstract: Abstract. We demonstrate the effectiveness of using hydrogen-doped argon as the support gas for the dielectric barrier discharge (DBD) ambient desorption/ionization (ADI) source in mass spectrometry. Also, we explore the chemistry responsible for the signal enhancement observed when using both hydrogen-doped argon and hydrogen-doped helium. The hydrogen-doped argon was tested for five analytes representing different classes of molecules. Addition of hydrogen to the argon plasma gas enhanced signals for gas-pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…An atmospheric‐pressure dielectric barrier discharge (AP‐DBD) configuration operated at atmospheric pressure and supplied with an argon‐hydrogen mixture was selected, owing to its suitability for the treatment of large surfaces . A 97.5:2.5 argon–hydrogen plasma gas composition was selected to maximize the concentration of reactive hydrogen species that favor the low‐temperature reduction of MOD ink and promote a non‐thermal desorption of the ligands . In contrast to our previous work, where the plasma‐assisted inkjet printing of silver required numerous fast and short inkjet printing/plasma‐enhanced sintering cycles (ca.…”
Section: Resultsmentioning
confidence: 99%
“…An atmospheric‐pressure dielectric barrier discharge (AP‐DBD) configuration operated at atmospheric pressure and supplied with an argon‐hydrogen mixture was selected, owing to its suitability for the treatment of large surfaces . A 97.5:2.5 argon–hydrogen plasma gas composition was selected to maximize the concentration of reactive hydrogen species that favor the low‐temperature reduction of MOD ink and promote a non‐thermal desorption of the ligands . In contrast to our previous work, where the plasma‐assisted inkjet printing of silver required numerous fast and short inkjet printing/plasma‐enhanced sintering cycles (ca.…”
Section: Resultsmentioning
confidence: 99%
“…These ions have been observed with flowing afterglow MS (Adams, Bohme, & Ferguson, 1970) and β‐particle ionization of rare gas hydrogen mixtures (Aquilanti et al, 1965), so their presence in a mixed gas plasma and participation in ionization processes is reasonable. In a follow‐up study, a similar signal enhancement was observed when hydrogen was doped into the argon plasma gas of an RF discharge (Ellis et al, 2016). In this case, the proton‐transfer reagents could include H 2 + , ArH + , Ar 2 + , ArH 2 + , H 3 + , and H + .…”
Section: Plasma Ionization For Organic Msmentioning
confidence: 61%
“…, or even high-energy photons [29,41]. Both HeH + and H 3 + , at m/z 5 and 3, respectively, are too low of mass to be detected by the MS instruments used here or by Farnsworth et al [29,40,41]. Meanwhile, the role and contribution of vacuum-ultraviolet photoionization with mixed-gas FAPA will be the focus of a future publication.…”
Section: He:h 2 -Fapa Source For Mass Spectrometrymentioning
confidence: 89%
“…Schütz et al [39] presented a survey emission spectrum from an argon-propane DBDI source that, ultimately, was shown to produce similar analyte ions and analytical performance to a helium 5 DBD. Farnsworth et al [29,40,41] has used a combination of emission, fluorescence, and absorption spectroscopies to monitor changes in helium species, particularly helium metastable atoms (He m ), in helium and He:H 2 DBD source. We draw on these earlier works to better understand plasma processes occurring in the mixed-gas FAPA sources tested here.…”
Section: Introductionmentioning
confidence: 99%